Disease and Treatment Patterns Among Patients With Pouch-related Conditions in a Cohort of Large Tertiary Care Inflammatory Bowel Disease Centers in the United States. Issue 3 (24th July 2020) - Barnes, Edward L; Raffals, Laura; Long, Millie D; Syal, Gaurav; Kayal, Maia; Ananthakrishnan, Ashwin; Cohen, Benjamin; Pekow, Joel; Deepak, Parakkal; Colombel, Jean-Frederic; Herfarth, Hans H; Sandler, Robert S
Abstract: Background: Gaps exist in our understanding of the clinical course of pouch-related disorders. Methods: We evaluated baseline disease activity and longitudinal treatment patterns among patients with inflammatory conditions of the pouch. Results: Among 468 patients with an ileal pouch-anal anastomosis (IPAA), 94 (20%) had acute pouchitis, 96 (21%) had chronic pouchitis, and 192 (41%) had Crohn disease of the pouch. Following an IPAA, 38% of patients were treated with a biologic and 11% underwent inflammatory bowel disease- or bowel-related surgery. Conclusions: Treatment patterns after IPAA indicate that pouch-related disorders have a significant impact on individual patients and the healthcare system. Lay Summary: In a multicenter longitudinal cohort from 7 academic centers, a significant burden of inflammatory conditions of the pouch was demonstrated after restorative proctocolectomy with ileal pouch-anal anastomosis for ulcerative colitis.